Nancy Drew Season 1 Disc 4 - McMann, Kennedy, 1996-; Lewis, Leah, 1996-; Jaizani, Maddison; CBS Studios Inc.; CBS DVD (Firm) (New York, NY CBS Studios, 2020)
Nancy Drew is a brilliant teenage detective whose sense of self had come from solving mysteries in her hometown of Horseshoe Bay, Maine, until her mother's untimely death derails Nancy's college plans. Devastated by her mother's passing, Nancy swears off crime-solving while crossing off the days until she can re-apply to college. But when a socialite is murdered, Nancy finds herself a prime suspect in the crime, along with a group of other teens present at the scene.
The Terror Of Horseshoe Bay; The Haunting Of Nancy Drew; The Girl In The Locket; and The Clue In The Captain's Painting.
Title from container.
Originally broadcast as single episodes of a television program from 2019-2020.
Wide screen (16:9).
Kennedy McMann, Leah Lewis, Maddison Jaizani, Tunji Kasim, Alex Saxon, Riley Smith.
Rating: Not rated.
DVD, region 1, NTSC, wide screen (16:9); Dolby digital 5.1.
Keywords: Drew, Nancy -- (Fictitious character) -- Drama; Teenagers -- Drama; Criminal investigation -- Drama; Detective and mystery television programs; Drama; Television programs